COMPENSATION POLICY AND ITS IMPACT ON PUBLIC SECTOR WORKFORCE MORALE AND PERFORMANCE IN EKITI STATE - Fasanya, Olubunmi Adeola; Okoro, Chinedu Ifeanyi (International Research Journal of Arts and Communication, 2024)
Compensation is a critical aspect of an employee's relationship with their employer. It refers to the number of wages and benefits that an employee receives for their services. This study aims to investigate the relationship between compensation and employee performance in Ekiti State. The study's specific objectives are to examine the impact of promotion, salary increases, and recognition on employee performance. A quantitative research design was used, and data was collected using a structured questionnaire from 200 employees in different organizations in Ekiti State. Descriptive statistics and regression analysis were used to analyze the data. The results revealed that promotion has a significant positive impact on employee performance, while salary increases have a moderate positive impact. Recognition was found to have a strong positive impact on employee performance. The study concludes that compensation is a crucial factor in attracting, retaining, and motivating employees. Employers should ensure that their compensation packages are competitive and include non-monetary benefits such as recognition. The study has important implications for both employers and employees in Ekiti State and beyond.